Comparison of Different Heat Stress Indices for Assessing Farmers' Exposure to Heat Stress - Masoud HAMEREZAEE; Somayeh FARHANG DEHGHAN; Farideh GOLBABAEI; Asad FATHI; Zahra ZAMANIAN (Tehran University of Medical Sciences, 2020)
No Abstract